2018
DOI: 10.21037/jtd.2018.04.124
|View full text |Cite
|
Sign up to set email alerts
|

Uniportal vs. triportal video-assisted thoracic surgery in the treatment of primary pneumothorax—a propensity matched bicentric study

Abstract: Background: The role of triportal video-assisted thoracoscopic surgery (VATS) is widely recognized for the treatment of primary spontaneous pneumothorax (PSP). The aim of this study was to assess the effectiveness and the potential advantages of uniportal VATS (U-VATS) for the treatment of PSP compared with triportal VATS. Methods: A total of 104 triportal (n=39) and uniportal (n=65) VATS procedures where performed for the treatment of PSP in two University hospitals. The prospectively collected data of postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
1
16
1
Order By: Relevance
“…They also showed that the SP group had significantly less pain on the same day, the first day, and the second day of the operation. Nachira et al [7] showed no significant difference between the SP and three-port VATS groups in terms of mortality, recurrence, and complications and reported that SP-VATS technique was clinically as safe as three-port VATS technique. The results of a recent meta-analysis also support these findings.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…They also showed that the SP group had significantly less pain on the same day, the first day, and the second day of the operation. Nachira et al [7] showed no significant difference between the SP and three-port VATS groups in terms of mortality, recurrence, and complications and reported that SP-VATS technique was clinically as safe as three-port VATS technique. The results of a recent meta-analysis also support these findings.…”
Section: Discussionmentioning
confidence: 97%
“…[6] Compared to open surgery, it has been clearly shown that traditional VATS has a greater advantage in terms of shorter postoperative stay, operative time, and duration of chest tube drainage and less postoperative pain, and more rapid recovery due to its less invasive nature. [7][8][9] Video-assisted thoracoscopic surgery using a SP is a safe and effective approach for the surgical treatment of pneumothorax. [5] An acceptable rate of recurrence, better patient satisfaction, and improved tolerability are shown in the VATS technique.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 However, surgery should also be selected strictly based on the risk factors and the patients' wishes to avoid overtreatment. 8 U-VATS may have advantages over a multiport procedure in terms of postoperative pain, 9,10 but high-quality evidence is still lacking. The major concern of U-VATS is the collision of the instruments through a single port, necessitating a relatively long skin incision (at least >20 mm).…”
Section: Discussionmentioning
confidence: 99%